ZOLEDRONATE-ASSOCIATED RECURRENCE OF OSTEONECROSIS OF JAWS - Rosen Tsolov; Elena Firkova; Georgi Yordanov; Silvia Tsvetkova-Trichkova (Peytchinski Publishing, 2020)
Medication-related osteonecrosis of the jaws is a commonly reported complication in patients receiving antiresorptive medications. We report a case of bone necrosis followed by comparatively fast recurrence in a patient with intravenous administration of zoledronic acid. The purpose is to focus the attention of dental practitioners on the possibility of recurrence and the importance of regular check-ups since preventive measures today are one of the most important management strategies for patients treated with zoledronate.